Reproductive behaviour of sneaker males of the peacock blenny - Gonçalves, David (2012)
In the peacock blenny Salaria pavo small sneaker males tried to steal ‘fertilizations’ at most in two different nests of large nesting males throughout the breeding season and spent most of their time associated with a particular nest. Sneakers did not associate with ripe females. As nesting males were the limiting reproductive resource in this population due to the scarcity of appropriate nest sites, sneakers were likely to maximize their chances of achieving parasitic fertilization of eggs by associating with successful nests.